Health-Related Quality of Life at 30 Days Among Indian Patients With Acute Myocardial Infarction: Results From the ACS QUIK Trial. Issue 2 (February 2019) - Huffman, Mark D.; Mohanan, Padinhare P.; Devarajan, Raji; Baldridge, Abigail S.; Kondal, Dimple; Zhao, Lihui; Ali, Mumtaj; Spertus, John A.; Chan, Paul S.; Natesan, Syam; Abdullakutty, Jabir; Krishnan, Mangalath N.; et al.
Abstract : Background: Despite a high cardiovascular disease burden, data on patient-reported health status outcomes among individuals with cardiovascular disease in India are limited. Methods and Results: Between November 2014 and November 2016, we collected health-related quality of life data among 1261 participants in the ACS QUIK trial (Acute Coronary Syndrome Quality Improvement in Kerala). We used a translated, validated version of the Seattle Angina Questionnaire administered 30 days after discharge for acute myocardial infarction, wherein higher scores represent better health status. We compared results across sex, myocardial infarction type, and randomization status using regression models that account for clustering and temporal trends. Mean (SD) age was 60.8 (13.7) years, 62% were men, and 63% presented with ST-segment–elevation myocardial infarction. More than 2 out of 5 respondents (44%) experienced angina 30 days after hospitalization, but most (68% of respondents with angina; 27% of the total sample) experienced it less than once per week (Seattle Angina Questionnaire angina frequency score 60). Respondents rated high median (interquartile range [IQR]) scores for angina frequency (100.0 [80.0–100.0]) overall with similar unadjusted scores by sex, but between-hospitality variability was high. Median (IQR) physical limitation scale response was 58.3 (41.7–77.8), which is consistent with limitations in moderate- and high-intensity activities at 30-day follow-up. Older respondents had more angina frequency and physical limitations and lower treatment satisfaction and quality of life. Women had greater physical limitations (median [IQR], 52.8 [38.9–72.2] for women versus median [IQR], 61.1 [44.4–80.6] for men; P <0.01). Overall treatment satisfaction was high with median (IQR) score, 81.3 (75.0–93.8), but overall quality of life was lower with median (IQR) score, 66.7 (50.0–83.3). Allocation to the quality improvement intervention group had the strongest direct association with higher quality of life (difference, 4.2; P =0.03), but overall effects were modest. Conclusions: This study represents the largest report of quality of life among myocardial infarction survivors in India with variability across age, sex, and quality improvement intervention status. Wide variability demonstrated across hospitals warrants further study. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02256657. Abstract : Supplemental Digital Content is available in the text.